The Relationship of Knowledge with Hand Washing Behavior in Students During The Covid 19 Pandemic - Saraswati, Rina; Setyo, Ilham Yoga; Sarwono, Sarwono (Prosiding University Research Colloquium, 2022)
Based on Basic Health Research (2018), the percentage of washing hands in children in Indonesia reaches 49.8%, in Central Java Province it reaches 45.0%, and in Cilacap Regency it is 38.5%. The behavior of washing hands is an act of hand hygiene to prevent transmission of covid-19, based on the results of interviews conducted on students, it was found that 7 out of 10 students did not know how to wash hands properly, and 6 out of 10 students said they did not wash their hands before eating. One of the factors that can influence behavior is knowledge. The aim of this research is to determine the relationship between knowledge and hand washing behavior in students during the covid-19 pandemic. This study uses a quantitative correlation method using cross-sectional design, the sampling technique uses a total sampling with 65 respondents. The instrument used is a knowledge questionnaire and a hand washing behavior questionnaire. The results of the study showed that knowledge of hand washing was in the good category of 31 students (47.7%), 29 students (44.6%), and less than 5 students (7.7%). As for the behavior of washing hands with good category as many as 28 students (43.1%), only 21 students (32.3%), and less as many as 16 students (24.6%). The results of the analysis chi- square obtained a p-value of 0.005, which means that there is a relationship between knowledge and the behavior of washing hands. The conclusion of this study shows that there is a relationship between knowledge and hand washing behavior in students during the covid-19 pandemic.